Evaluación in-vitro de la eficacia de tres solventes de Gutapercha en el periodo marzo-julio 2015 - Villavicencio Vallejo, Karina Estefanía (2015)
The objective of this research was to evaluate the effectiveness of in vitro dissolution of the gutta organic solvents: xylol traditional use and essential oils: orange oil and eucalyptol, recent use, given the frequent need to remove blockages in the duct root retreat procedures. The study was conducted on eighty single-rooted teeth sealed, being equally divided into three experimental groups (xylol, eucalyptol and orange oil) and a control group (saline) for 5 to 10 minutes and then is dried at room temperature for 24 hours. The solvent effectiveness was recorded in grams weight loss in a digital balance (Ohaus), calculating the difference between the pre and post immersion weight immersing the samples for each experimental time. It is obtained as a result that all solvents are effective for dissolving gutta regardless of the exposure time without a statistically significant difference between weight losses. Eucalyptus was the one who caused more weight loss after 5 minutes with 0.00914 followed by Orange Oil after 10 minutes with a loss of 0.00698; the Xylol solvent was less weight loss obtained at both 5 and 10 minutes by the technique used and rapid evaporation. Keywords: Endodontic, Gutta-percha, Organic Solvents, Xylene, eucalyptol, orange oil.